Comparative analysis of the thermal stability of the triflate, tosylate and tetrafluoroborate diazonium salts - Bondarev A. A. Aleksandr Aleksandrovich; Naumov E. V. Evgeny Vladimirovich; Kasanova A. Zh. Asiya Zhursunovna; Krasnokutskaya E. A . Elena Aleksandrovna; Filimonov V. D. Viktor Dmitrievich (Section 2: Thermal analysis and calorimetry of organic substances and materials, 2016)
They were synthesized tosylate, triflate, tetrafluoroborate 4-nitrophenildiazonium and 4-methoxyphenyldiazonium triflate. Thermal decomposition of the salts was studied by TGA/DSC. Autocatalytic kinetic parameters of the decomposition reaction in isothermal conditions were identified. Storage safety assessment is produced using STANAG procedures. The study methoxy derivatives safer to store than nitro compounds but the heat flow for diazonium salts exceed the allowable values.